2017
DOI: 10.1016/j.ygyno.2017.02.016
|View full text |Cite
|
Sign up to set email alerts
|

MELK expression in ovarian cancer correlates with poor outcome and its inhibition by OTSSP167 abrogates proliferation and viability of ovarian cancer cells

Abstract: MELK inhibition by OTSSP167 may thus present a strategy to treat patients with aggressive, progressive, and recurrent ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 38 publications
7
55
0
Order By: Relevance
“…MELK has been reported as an important regulator of the G2/M transition in many studies. 16,[22][23][24] In contrast, MELK silencing was found to contribute to the delay of S phase progression by Beke et al and Kig et al 13,30 Our study Figure S3). Owing to the lack of additional tumour cell lines, we could not conclude that p53 affects the role of MELK in the cell cycle.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…MELK has been reported as an important regulator of the G2/M transition in many studies. 16,[22][23][24] In contrast, MELK silencing was found to contribute to the delay of S phase progression by Beke et al and Kig et al 13,30 Our study Figure S3). Owing to the lack of additional tumour cell lines, we could not conclude that p53 affects the role of MELK in the cell cycle.…”
Section: Discussionmentioning
confidence: 59%
“…[8][9][10][11][12][13] It has been shown that MELK is overexpressed in multiple human tumours, including the following: melanoma, 8 diffuse intrinsic pontine glioma (DIPG), 14 breast cancer, 6,15 gastric cancer, 16 high-grade prostate cancer, 17 hepatocellular carcinoma, 18 kidney cancer, 19 small lung cancer, 20 myeloma, 21 acute myeloid leukaemia (AML) 22 and chronic lymphocytic leukaemia (CLL). 15,23,24 Further, genomic or pharmacologic inhibition of MELK has been shown to suppress tumour growth in vitro and in pre-clinical adult cancer models, indicating that this kinase is a potential therapeutic target. 15,23,24 Further, genomic or pharmacologic inhibition of MELK has been shown to suppress tumour growth in vitro and in pre-clinical adult cancer models, indicating that this kinase is a potential therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To test whether MELK inhibition would block melanoma growth, we treated melanoma cell lines with the MELK inhibitor OTSSP167 (Chung et al, 2012; Kohler et al, 2017; Wang et al, 2014). OTSSP167 treatment significantly inhibited melanoma cell line proliferation (Figure 2A) and colony formation in a soft-agar assay (Figure 2B–C and Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, MELK knockout mice are viable and display no adverse phenotypes (Wang et al, 2014). This information and the availability of small-molecule inhibitors of MELK with anti-cancer activity in breast and other cancers indicates that MELK might be a druggable target for cancer cell-selective therapy (Gray et al, 2005; Kohler et al, 2017; Nakano et al, 2005). …”
Section: Introductionmentioning
confidence: 99%